GURU SEBAGAI FASILITATOR DALAM MENGASAH KEMAMPUAN BERPIKIR KRISTIS SISWA PADA PEMBELAJARAN DARING - Marcellino Timoty Lukman; Year Rezeki Patricia Tantu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
At the elementary school level, students need to master basic concepts and develop critical thinking skills. In the midst of the times in 21st century, the ability to think critically becomes one of the skills that students need to master so that they can face the challenges of this century. Critical thinking skills can be trained through the learning process in the classroom. The reality in the field when carrying out online learning, there are 6th-grade elementary school students who have not been able to meet critical thinking indicators in Mathematics lessons, namely not understanding concepts (addition and subtraction), analyzing, and detecting requirements on Mathematics problems. This is also because the teacher has not facilitated students to be the ability to hone students critical thinking skills well. The purpose of this study is to explain the role of teachers as facilitators in honing the critical thinking skills of 6th-grade students in mathematics online learning. The research was conducted using descriptive qualitative methods at one of the schools in Tangerang. The results and conclusions were obtained that the role of the teacher as a facilitator was able to hone the critical thinking skills of 6th-grade students in mathematics online learning through providing learning media in the form of learning games, learning videos, and worksheet, as well as providing feedback and guidance to students in solving Mathematics problems.